2020
DOI: 10.3389/fmed.2020.585792
|View full text |Cite
|
Sign up to set email alerts
|

Part I: Accuracy of Teledermatology in Inflammatory Dermatoses

Abstract: Teledermatology is assuming a progressively greater role as a healthcare delivery method, especially now, during this pandemic time. It is important to know how accurate this tool is for different skin diseases. Most of the studies have focused on skin neoplasms or general dermatology. Studies based on a large number of inflammatory dermatoses have not yet been performed. Such knowledge can help dermatologists to decide whether endorsing this method or not. Our objective was to determine the accuracy of telede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…[12][13][14] Two retrospective studies from Brazil reported high degree of accuracy with teledermatology in inflammatory dermatoses and moderate accuracy for neoplasms. 15,16 High levels of satisfaction with teleservices has been reported previously in patients having acne. 17 In this study, 62% of acne patients reported being satisfied or very satisfied with teleconsultation services.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…[12][13][14] Two retrospective studies from Brazil reported high degree of accuracy with teledermatology in inflammatory dermatoses and moderate accuracy for neoplasms. 15,16 High levels of satisfaction with teleservices has been reported previously in patients having acne. 17 In this study, 62% of acne patients reported being satisfied or very satisfied with teleconsultation services.…”
Section: Discussionmentioning
confidence: 84%
“…[12][13][14] Two retrospective studies from Brazil reported high degree of accuracy with teledermatology in inflammatory dermatoses and moderate accuracy for neoplasms. 15,16 High levels of satisfaction with teleservices has been reported…”
Section: Discussionmentioning
confidence: 99%
“…Die Dermatologie hat sich für die Implementierung solcher Technologien aufgrund ihres hauptsächlich visuell orientierten Charakters bei der Diagnosestellung als ideales ärztliches Fach erwiesen. Zwar unterscheidet sich die diagnostische Trefferquote zwischen Studien, mehrheitlich wurden jedoch korrekte Diagnoseraten von 75-80% geschätzt, die vergleichbar der Präsenzvorstellung sind [11,12]. Für eine teledermatologische Betreuung gut geeignete Hauterkrankungen sind u. a. Akne vulgaris, atopische Dermatitis, Psoriasis, seborrhoische Dermatitis, bullöses Pemphigoid, Tinea pedis, Onychomykose und Xerosis cutis [13,14].…”
Section: Introductionunclassified
“…Today, with digital cameras, it is possible to store high-quality images and transmit them without distortion at a significantly lower cost, dramatically compared to a standard camera. 13 On the other hand, the increase in the number and quality of images, besides electronic devices limitation-storage capacities and data transfer bandwidth-have prompted engineers and image experts to find a way to address this challenge. Various algorithms can achieve this goal, which is defined as "image compression techniques".…”
Section: Introductionmentioning
confidence: 99%